Primary Carcinoid Tumor of the Prostatic Urethra: Case Report and Review of the Literature. (9th November 2022) - Potterveld, S K; Olson, D
Abstract: Introduction/Objective: We report a case of a 72-year-old male with a past medical history of previously treated urothelial cell carcinoma without recurrence in over ten years. Methods/Case Report: Surveillance cystoscopy revealed a small lesion involving the prostatic urethra. Microscopic examination of the prostatic urethra lesion revealed a proliferation of pseudoglandular structures within the lamina propria adjacent to an area of urothelial cystitis cystica et glandularis. The pseudoglandular structures contained primarily small bland nuclei with fine chromatin and featured frequent intracytoplasmic neuroendocrine granules. Scattered foci of enlarged hyperchromatic nuclei were present, but no necrosis or increased mitotic activity was identified. Immunohistochemistry revealed the lesional cells were diffusely positive for chromogranin and synaptophysin; while negative for GATA3 and NKX3.1. The histologic features and immunoprofile are characteristic of primary carcinoid tumor of the prostatic urethra, which uniquely shows a predominantly pseudoglandular architecture compared to carcinoid tumors of other sites and are often associated with reactive urothelial proliferations. Results (if a Case Study enter NA): NA. Conclusion: Acknowledgement of this rare entity as a diagnostic mimicker is critical to ensure proper treatment and management of the patient.